A Single Case Study On Tundikari (Acute Tonsillitis) Treated With Shaman Aushadhi - Das, Madhumita; Nematullah, Md; Mahapatra, P B Kar (International Research Journal of Ayurveda & Yoga, 2021)
In Ayurveda Tundikari is described under Mukharoga, which is characterized by Jwara (fever), Pradaha (burning sensation), Vedana (pain), Sotha (swelling), Galadhakaranapida (pain during deglutition). Tundikari may be correlated with tonsillitis. Inflammation of the tonsil is known as tonsillitis. Tonsillitis most commonly occurs in pediatric age groups. The incidence of this disease is about 7% of all visits to pediatrician. In the present study a 15 years old male patient suffering from tundikari (acute tonsillitis), since last 3 days. He was treated with Ayurvedic Shaman aushadi (kanchanar Guggulu, Laxmivilas Rasa, Khadira Vati) which gives an effective result.